THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP TO THE SOLDIER PERFORMANCE WITH HUMAN RESOURCE DEVELOPMENT AS THE INTERVENING VARIABLE AT THE BATTALION KOMANDO 469 KOPASGAT - Agil Gillan Gumilar; Marbawi; Anwar Puteh (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to determine the influence of transformational leadership to soldier Performance through human resources development of the command battalion 469 Kopasgat. The data used is primary data by distributing questionnaires to 171 employees of the command battalion 469 Kopasgat. Data analysis method used is structural modeling and processed with the help of analysis of the moment structural (AMOS) application program. The result of the Research shows that there is the influence of transformational leadership influence of human resources development, then transformational leadership and human resources development influence of soldier performance of the command battalion 469 Kopasgat; furthermore, the results of the study found human resources development variables function partially mediate the relationship of transformational leadership to the soldier performance of the command battalion 469 Kopasgat.